1957
DOI: 10.1017/s0007485300002935
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Crop Loss following Insect Attack on Cotton in East Africa

Abstract: The loss of crop following insect attack on cotton was studied in 1950–54 at the Cotton Research Station, Namulonge, which is situated in the elephant-grass zone of Uganda, in which the principal pest of cotton was originally considered to be Lygus vosseleri Popp. In 1953, the main invasion of cotton by Lygus occurred during September and October, originating from cultivated crops of black gram (Phaseolus mungo) and sorghum and from the wild perennial legume, Pseudarthria sp., which earlier workers had conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

1957
1957
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 7 publications
4
14
0
Order By: Relevance
“…That pest damage in the elephant-grass zone is negligible is supported by McKinlay & Geering (1957) and Coaker (1957), and by the results with dicrotophos where final yields were unaffected although bollworm was not controlled. Clearly the plants compensate for insect damage incurred in this zone, and the inability of the plant to mature more fruiting bodies under a given set of conditions is the true limiting factor.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…That pest damage in the elephant-grass zone is negligible is supported by McKinlay & Geering (1957) and Coaker (1957), and by the results with dicrotophos where final yields were unaffected although bollworm was not controlled. Clearly the plants compensate for insect damage incurred in this zone, and the inability of the plant to mature more fruiting bodies under a given set of conditions is the true limiting factor.…”
Section: Discussionmentioning
confidence: 83%
“…3) have the same form as those of McKinlay & Geering (1957) and Coaker (1957). Analysis of the yields of total and clean seed cotton showed that there were no significant differences between treatments at any of the seven picking dates or between the final yields of total seed cotton or clean seed cotton (Table IV) cotton (angular transformation) showed a significant difference (P < 0-05) between treatments, with dicrotophos having significantly (P < 0-01) more stained cotton than any other treatment.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations